Respiratory symptoms in older people and their association with mortality - Hewitt, J (BMJ Group, 2005)
Methods: A total of 14 458 people aged 75 years and over participating in a trial of health screening of older people in general practice answered questions on three respiratory symptoms: cough, sputum production, and wheeze. The association of symptoms with mortality was examined for all cause and respiratory causes of death taking account of potential confounders. Results: Coughing up phlegm in winter mornings had a prevalence of 27.0% (95% confidence interval (CI) 26.8 to 27.2). Those with this symptom had an adjusted hazard ratio for all cause mortality of 1.35 (95% CI 1.21 to 1.50), p<0.001 and for respiratory specific mortality of 2.01 (95% CI 1.66 to 2.41), p<0.001. Phlegm at any time of the day in winter had a prevalence of 16.5% (95% CI 16.3 to 16.7) with hazard ratios for all cause and respiratory specific mortality of 1.28 (95% CI 1.15 to 1.42) and 2.28 (95% CI 1.92 to 2.70), p<0.001. Wheeze or whistling from the chest had a prevalence of 14.3% (95% CI 14.1 to 14.5) with hazard ratios of 1.45 (95% CI 1.31 to 1.61) and 2.86 (95% CI 2.45 to 3.35), p<0.001. Conclusions: The prevalence of respiratory symptoms is widespread among elderly people and their presence is a strong predictor of mortality.